ISLAMIC EDUCATION AT JUNIOR HIGH SCHOOL LEVEL: DIFFERENCES IN CURRICULUM STRUCTURE, LEARNING METHODS, AND THEIR IMPACT ON STUDENTS' UNDERSTANDING OF ISLAMIC CONCEPTS - Wilda Rizkiyahnur Nasution; Al-Amin (CV. ADIBA AISHA AMIRA, 2025)
This study analyses the differences in curriculum structure and teaching methods in Islamic Religious Education at public junior high schools, private Islamic junior high schools, and modern Islamic boarding schools, as well as their impact on students' understanding of Islamic concepts. Using a descriptive-comparative qualitative literature review approach, the study compares the national Merdeka Curriculum, which focuses on the fundamentals of faith and jurisprudence, with the expansive private model, which includes Arabic memorisation and Arabic language, as well as pesantren-based mastery learning using classical Islamic texts. Teaching methods varied from conventional es in public schools, student-centred through discussion-projects in private schools, to hybrid sorogan-bandongan in Islamic boarding schools. The results show a gradation of understanding, with state schools excelling in breadth but lacking in depth, private schools integrating cognitive and affective learning, and Islamic boarding schools dominating in higher-order thinking skills, supported by a positive correlation between curriculum intensity and concept retention. A hybridised curriculum is recommended to optimise holistic Islamic literacy.